Synthesis, structure and spectroscopic properties of oxovanadium tris(3,5-dimethylpyrazolyl)borate aroylthiourea complexes - Syahidah Mohd Tahir,; Aisha Al-Abbasi,; Qurnisha Ghazali,; Khuzaimah Arifin,; Mohammad Kassim, (Penerbit Universiti Kebangsaan Malaysia, 2018)
Aroylthiourea ligands, 1-aroyl-3-cyclohexyl-3-methylthiourea (HL1), 1-(2-chloroaroyl)-3-cyclohexyl-3-methylthiourea (HL2), 1-(3-chloroaroyl)-3-cyclohexyl-3-methylthiourea (HL3) and 1-(4-chloroaroyl)-3-cyclohexyl-3-methylthiourea (HL4) were synthesized through a condensation reaction of methylcyclohexylamine and aroylisothiocyanate with a general formula (X-Ph)(CO)NH(CS)N(C6H5)(CH3) where X = H, o-Cl, m-Cl and p-Cl, fully characterized by CHNS micro elemental analysis, infrared spectroscopy, UV-visible, nuclear magnetic resonance (1H, 13C) and X-ray crystallography. 1-(3-chloroaroyl)-3-cyclohexyl-3-methylthiourea (HL3) crystallized in the monoclinic system, a=14.504(3), b=4.9599(11), c=22.325(5) Å, β=98.461(7)°, Z= 4 and V=1588.5(6) Å with space group P21/c. The IR spectra of the ligands exhibits the characteristic v(CO) and v(N-H) at range 1701-1640 cm-1 and 3317-3144 cm-1, respectively. Whereas the 1H and 13C NMR spectra shows the resonances for N-H and -CO groups at range 8.3-8.5 and 160-163 ppm, respectively. A one-pot reaction involving the aroylthiourea ligand, oxovanadium(IV) ion and potassium hydrotris(3,5-dimethylpyrazolyl)borate (KTp*) complex gave the desired [oxovanadium(IV)(tris(pyrazolyl)borate)(aroylthiourea)] complexes namely Tp*VOL1, Tp*VOL2, Tp*VOL3 and Tp*VOL4 and all complexes were characterized accordingly. X-ray study showed that Tp*VOL1 adopted a monoclinic crystal, a=3.415(2), b=19.463(3), c=14.22(3) Å, β=107.411(4)°, Z= 4 and V=3542.7(11) Å with P21/c space group. The VO2+ center adopted a pseudo-octahedral geometry O2N3S, with the oxovanadium(IV) coordinated to the bidentate ligand (X-Ph)(CO)NH(CS)N(C6H5)(CH3) and tridentate Tp* ligands. The results showed that aroylthiourea ligands behave as bidentate chelate through O and S atom and the Tp* C3v symmetry adds stabilization to the VO2+ through its protective tripodal geometry.